Античность. Средние века. Раннее Возрождение - Арган Джулио Карло (1990)
Экземпляры: ЦБ (20231124) / Инвентарный номер: 25308 / Цена: 6.50 / Сис.шифр: 85.103 / Авт.знак: А 79 / ГРНТИ: 18 / ББК: 85.103